The Effectiveness of implementing pre-reading plan (prep) strategy toward the students Reading comprehension - MUHAMMAD FERRY OCTA ALFARICY; Fetriani Fetriani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT Muhammad Ferry Octa Alfaricy, 2025. “The Effectiveness of Implementing Pre-Reading Plan (Prep) Strategy Toward the Students Reading Comprehension”. Thesis: English Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Bengkulu. Supervisor: Fetriani, M.Pd. This study aims to investigate the effect of the Pre-Reading Plan (PReP) strategy on the reading comprehension of second-semester English Education students at Muhammadiyah University of Bengkulu. In this research, a quantitative approach with a quasi-experimental design was employed, specifically a pre-test–post-test control group design. The population comprised all second-semester students, with total sampling used to assign two classes as the experimental and control groups. A reading comprehension test was administered to both groups before and after the treatment. Data were analyzed using an Independent Samples T-Test in SPSS. The results showed that the p-value (0.731) > 0.05, indicating no statistically significant difference between the groups. However, descriptively, the experimental group demonstrated greater improvement in scores compared to the control group, suggesting that the PReP strategy had a positive influence on students’ reading comprehension. Keywords: Pre-Reading Plan, Reading Comprehension, Quasi-Experimental.